Abundance of d‐2‐hydroxyglutarate in G2/M is determined by FOXM1 in mutant IDH1‐expressing cells. Issue 16 (4th July 2019) - Bala Bhaskara Rao, Kancharana; Katragunta, Kumar; Sarma, Uma Maheswara; Jain, Nishant
Abstract : Isocitrate dehydrogenases (IDHs) are metabolic enzymes that are mutated in several cancers, resulting in overproduction ofd ‐2‐hydroxyglutarate (D‐2HG). However, the signalling pathways and factors that regulate mutant IDHs or their metabolites remain elusive. Here, we report that in synchronized cells and cells treated with anti‐mitotic agents, wild‐type and mutant IDH proteins are induced maximally in G2/M. Moreover, mutant IDH1‐expressing cells arrested in G2/M harbour high D2HG levels. Genetic or pharmacological perturbation of Forkhead box protein M1 (FOXM1) abrogates the levels of IDH1 mRNA, protein and D2HG in G2/M. Conversely, overexpression of FOXM1 or hyperactive FOXM1 activates the IDH1 promoter and increases the abundance of its protein levels. In summary, our results show that in G2/M, higher D2HG levels are dependent on FOXM1‐mediated transcription of IDH1. Abstract :